2022
DOI: 10.1001/jamanetworkopen.2021.42676
|View full text |Cite
|
Sign up to set email alerts
|

Drug Overdose Mortality Among People Experiencing Homelessness, 2003 to 2018

Abstract: IMPORTANCEDespite high rates of drug overdose death among people experiencing homelessness, patterns in drug overdose mortality, including the types of drugs implicated in overdose deaths, remain understudied in this population. OBJECTIVE To describe the patterns in drug overdose mortality among a large cohort of people experiencing homelessness in Boston vs the general adult population of Massachusetts and to evaluate the types of drugs implicated in overdose deaths over a continuous 16-year period of observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
52
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 36 publications
(60 reference statements)
5
52
0
1
Order By: Relevance
“…45 White PEH may thus be more likely to experience more intense weathering and early onset of age-related conditions. 24,46 We note that this finding is also consistent with recent studies of the intersectional effects of adverse circumstances and race and ethnicity on allostatic load, which have found that advantages for White individuals are less pronounced among disadvantaged than advantaged groups. 47,48 The pattern of excess mortality risk among Hispanic PEH is striking, both relative to the general Central American descent, without a high school degree, or working in industries including food, agriculture, and manufacturing.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…45 White PEH may thus be more likely to experience more intense weathering and early onset of age-related conditions. 24,46 We note that this finding is also consistent with recent studies of the intersectional effects of adverse circumstances and race and ethnicity on allostatic load, which have found that advantages for White individuals are less pronounced among disadvantaged than advantaged groups. 47,48 The pattern of excess mortality risk among Hispanic PEH is striking, both relative to the general Central American descent, without a high school degree, or working in industries including food, agriculture, and manufacturing.…”
Section: Discussionsupporting
confidence: 91%
“… 45 White PEH may thus be more likely to experience more intense weathering and early onset of age-related conditions. 24 , 46 We note that this finding is also consistent with recent studies of the intersectional effects of adverse circumstances and race and ethnicity on allostatic load, which have found that advantages for White individuals are less pronounced among disadvantaged than advantaged groups. 47 , 48 …”
Section: Discussionsupporting
confidence: 91%
“…Compared to the control group, SIRI team patients had lower rates of discharge to homelessness and higher rates of residential addiction treatment. Preventing the known harms of homelessness among persons with SUD is a third potential contributor to the intervention's impact [ 35 ]. Additionally, SIRI team patients identified trust in the team, harm reduction focus, patient advocacy, and nonstigmatizing care as strengths of the intervention, which may have also facilitated the team's effectiveness [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…One final potential contributor is the movement of individuals experiencing homelessness into temporary housing facilities during the pandemic given high risk of viral transmission in congregate shelters [ 52 ]. This may have reduced overdoses given the strong link between the experience of homelessness and drug overdoses [ 19 , 53 , 54 ]. The rebound observed in the re‐opening period may be explained by movement of residents out of such temporary housing facilities or a decline in the potential protective effects of housing on overdoses over time—especially in the absence of additional wraparound supports [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The outsized direct impact of the pandemic on the homeless population and their pre‐existing risk factors present concerns about disproportionate indirect impacts, particularly in relation to substance‐related outcomes. Drug overdose is a leading cause of morbidity and mortality in the homeless population and baseline rates of substance use disorders are several‐fold higher among individuals experiencing homelessness compared to their housed counterparts [ 19 , 20 , 21 ]. Individuals experiencing homelessness stand to benefit greatly from substance use treatments and harm reduction services [ 22 ].…”
Section: Introductionmentioning
confidence: 99%